Pengaruh Struktur Kepemilikan Keluarga terhadap Kinerja Perusahaan pada Sektor Pertambangan - Novi Dwi Vivian Thejakusuma; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Most of the firms in Indonesia are still dominated by family. Family firms have advantages and disadvantages that can affect their performance. Previous researches on the affect of family ownership structure on firm performance were still inconsistent. This study aimed to identify and to prove the affect of family ownership structure on firm performance. Firm performance was measured by using ROA and the control variables used were GCG score and firm risk. This research was carried on mining sector companies listed on IDX in 2010-2015 with a sample of 125 observations. The results showed a significant negative correlation between family ownership structure and firm performance. The results also showed that GCG score didn’t have affect on firm performance, while firm risk had significant negative affect on firm performance.